2006
DOI: 10.1021/ac060663k
|View full text |Cite
|
Sign up to set email alerts
|

Single-Walled Carbon Nanotubes Used as Stationary Phase in GC

Abstract: Single-walled carbon nanotubes (SWNTs) have high surface area, high adsorption ability, and nanoscale interactions. In this study, capillary columns including SWNTs, ionic liquid (IL), and IL + SWNTs for GC were prepared. The separation results showed that SWNTs possessed a wide selectivity toward alkanes, alcohols, aromatic compounds, and ketones, and a SWNT capillary column was a very useful GC column for the separation of gas samples. Coating the IL stationary phase on the SWNT capillary column, the SWNTs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 16 publications
(15 reference statements)
0
50
0
Order By: Relevance
“…Ionic liquid (IL), a kind of fascinating molten salt with nearly zero vapor pressure and high thermal stability [5][6][7], has demonstrated high affinity toward various kinds of solid, such as carbon nanotubes [8][9][10][11][12][13][14], silica [15][16][17] and clays [18]. Various interactions, including cation-π interaction [8][9][10][11]19], van der Waal forces [13], delocalized electron interaction [14] and hydrogen bonding [16,18] have been well acknowledged and therefore subjected to a plenty of applications [14,[16][17][18][20][21][22][23][24][25][26]. Thanks to these interactions, ILs with specific structure can be employed as possible interfacial modifiers for various filled polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquid (IL), a kind of fascinating molten salt with nearly zero vapor pressure and high thermal stability [5][6][7], has demonstrated high affinity toward various kinds of solid, such as carbon nanotubes [8][9][10][11][12][13][14], silica [15][16][17] and clays [18]. Various interactions, including cation-π interaction [8][9][10][11]19], van der Waal forces [13], delocalized electron interaction [14] and hydrogen bonding [16,18] have been well acknowledged and therefore subjected to a plenty of applications [14,[16][17][18][20][21][22][23][24][25][26]. Thanks to these interactions, ILs with specific structure can be employed as possible interfacial modifiers for various filled polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…The McReynolds constants [45][46][47] were usually used as the evaluation standard of stationary phase polarity. In this study, we chose benzene, 1-butanol, 2-pentanone, 1-nitropropane, and pyridine as the analytes for describing the polarity of [Zn 2 (D-Cam) 2 (4,4′-bpy)] n .…”
Section: Characterization Of the Mof-coated Open Tubular Columnmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) are attractive materials for the chromatographic stationary phase, and previous studies have demonstrated that CNTs have good separation ability due to chemical and thermal stability and a high surface-to-volume ratio [9][10][11][12]. These studies used a conventional steel, glass, or fused-silica column.…”
Section: Introductionmentioning
confidence: 99%
“…However, the previously reported use of CNTs as a GC stationary phase resulted in relatively low separation efficiency [5,[9][10][11][12]. Moreover, gas separation columns with a CNT stationary phase suffer from poor separation of high-boiling-point compounds [5,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation